Full stack FastAPI, React, and MongoDB fast-paced web app development with the FARM stack - Aleksendrić, Marko; Batra, Shrey; Palmer, Rachelle; Ranjan, Shubham (Packt Publishing Ltd., 2024)
Discover how to harness the power of the FARM stack-FastAPI, React, and MongoDB-to develop production-ready web applications of varying complexity. Written by a team of industry experts, including MongoDB champions and product leaders, this fast-paced, hands-on guide equips beginners with essential skills to build web applications efficiently. Introducing each element of the stack, the book demonstrates how to seamlessly integrate them to create a medium-sized web application. You'll set up MongoDB as a document store, construct a simple API with FastAPI, and build an application using React. The guide also covers enhancing application security through authentication and authorization with JSON Web Tokens. Beyond mastering the stack, you'll get to grips with integrating Large Language Models (like ChatGPT) for advanced functionality, such as automated email sending. Additionally, you'll learn how to make the most of Next.js 14, a robust full-stack framework offering improved developer experience. By the end of the book, you'll have created functional applications and gained the foundation to explore diverse and more specialized domains, expanding your development horizons.
Includes bibliographical references and index
Keywords: MongoDB; Application software -- Development; Web site development; Python (Computer program language); Software architecture; Logiciels d'application; Développement; Sites Web; Développement; Python (Langage de programmation); Architecture logicielle